MODEL KINERJA PEGAWAI DENGAN KECERDASAN INTELEKTUAL SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan BUMN di Kota Semarang) - Nurul Latifah; Lies Indriyatni (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
This study aims to examine and analyze the influence of competence, motivation and communication on employee performance with intellectual intelligence as a moderating variable. So it can be analyzed whether the intellectual intelligence variable can serve as moderating to the performance of employees.Variables in this study consisted of five variables where in the first stage of competence, motivation and communication variables become independent variables while employee performance becomes dependent variable. Then in the second stage the three independent variables are modified with intellectual  intelligence variables.Techniques of collecting research data by spreading questionnaires on employees of state-owned companies in Semarang City. The number of samples in this study amounted to 195 people. Analyzer used in this research is doubled linear regression, while to test the moderation variable by using MRA (Moderated Regression Analysis).